Meningkatkan Kesehatan Masyarakat Guna Mencapai Tujuan SDGs Melalui Penyuluhan Pengelolaan Air Bersih pada Masa Pandemi Covid-19 di Desa Kalimas Kabupaten Situbondo - Budhy S, Theresia Indah; Sudana, I Ketut; Rahmawati, Septyana Eka; Handayani, Roni (Jurnal Pengabdian UNDIKMA, 2022)
This community service aims to increase the knowledge of the residents of Kalimas Village about the importance of clean water management as an effort to improve public health in order to achieve the SDGs goals. the service method uses counseling that takes place offline and online to reduce the spread of Covid-19. The results of the service show that the community understands the importance of clean water for health. The construction of reservoirs is proof of the application of infrastructure that supports clean water treatment. The people of Kalimas Village still need material and non-material assistance to increase the SGDs (Sustainable Development Goals) index according to the government's target.